The first eigenvalue of p-Laplacian systems with nonlinear boundary conditions. (13th November 2005) - Kandilakis, D. A.; Magiropoulos, M.; Zographopoulos, N. B.
Abstract : We study the properties of the positive principal eigenvalue and the corresponding eigenspaces of two quasilinear elliptic systems under nonlinear boundary conditions. We prove that this eigenvalue is simple, unique up to positive eigenfunctions for both systems, and isolated for one of them.